Proceedings of the 2016 ACM Conference on Designing Interactive Systems 2016
DOI: 10.1145/2901790.2901866
|View full text |Cite
|
Sign up to set email alerts
|

"It just seems outside my health"

Abstract: To improve care for the growing number of older adults with multiple chronic conditions, physicians and other healthcare providers need to better understand what is most important in the lives of these patients. In a qualitative study of home visits with patients and family caregivers, we found that patients withhold information from providers when communicating about what they deem important to their health and well-being. We examine the various motivations and factors that explain communication boundaries be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…This may leave out values that providers do not perceive to be directly related to health care concerns. Our prior work [23] suggests that this communication boundary between patients' medical concerns and patients' values is reinforced by patient perceptions of what providers want to know. In that study, patients often did not disclose values freely because patients did not perceive their values to be pertinent to their health care.…”
Section: Encouraging Communication About Patient Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…This may leave out values that providers do not perceive to be directly related to health care concerns. Our prior work [23] suggests that this communication boundary between patients' medical concerns and patients' values is reinforced by patient perceptions of what providers want to know. In that study, patients often did not disclose values freely because patients did not perceive their values to be pertinent to their health care.…”
Section: Encouraging Communication About Patient Valuesmentioning
confidence: 99%
“…Our prior work has explored MCC patients' perspectives on communicating with providers about values [23]. Herein, we extend this work by adding providers' perspectives.…”
Section: Supporting Patient-provider Communication Through Interactivmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes the idea behind the progress bar more perceptible than using just bar charts or graphs as is the case in most applications available for monitoring physical activity (Walters et al, 2010). To enable patients to make sense of personal health information, it is necessary to exploit the patient"s perceptions to present targets and prescriptions (Lim et al, 2016). Figure 1.a shows a representation of the prescription in the mobile application interface.…”
Section: Correct Interpretation and Understandingmentioning
confidence: 99%
“…They identified gaps between the groups with implications on design and adoption of technology [35]. Another study revealed limitations of existing approaches to support patient-provider communication and identified challenges for the design of systems that honor patient needs and preferences [36].…”
Section: Emerging Research In Humancomputer Interactionmentioning
confidence: 99%